THE ROLE OF NURSES IN THE INVESTIGATION OF CERVICAL CANCERS AND BREAST CANCER: A BIBLIOGRAPHICAL REVIEW (CIPEEX, 2022)
INTRODUCTION: BREAST CANCER IS A MALIGNANT TUMOR THAT DEVELOPS IN BREAST TISSUE, BEING THE MOST FREQUENT IN THE FEMALE POPULATION WORLDWIDE AND IN BRAZIL, MAKING IT A SERIOUS PUBLIC HEALTH PROBLEM AND GENERATING HIGH MORTALITY RATES. CERVICAL CANCER IS AN EVOLUTIONARY DISEASE CHARACTERIZED BY CERVICAL DYSPLASIA THAT CAN PROGRESS TO AN INVASIVE STAGE IN THE SPACE OF 10 TO 20 YEARS, INITIALLY BY A PRECURSOR LESION. THESE CANCERS ARE DISEASES OF POSSIBLE EARLY DIAGNOSIS, THROUGH SIMPLE TESTS THAT CAN BE PERFORMED THROUGH THE NURSING CONSULTATION OR THE MULTIDISCIPLINARY TEAM. BREAST AND CERVICAL CANCERS HAVE BEEN MULTIPLYING EACH YEAR; IN BRAZIL, 57,960 AND 16,340 NEW CASES HAVE BEEN ESTIMATED FOR EVERY 100,000 WOMEN, RESPECTIVELY (INCA, 2017). OBJECTIVE: THE OBJECTIVE OF THIS STUDY WAS TO INVESTIGATE, ALONG WITH THE NATIONAL SCIENTIFIC LITERATURE, THE ATTRIBUTIONS OF NURSES TO THE DIAGNOSIS OF CERVICAL AND BREAST CANCERS. METHOD: THIS IS A BIBLIOGRAPHICAL REVIEW OF ARTICLES INDEXED IN THE VHL (VIRTUAL HEALTH LIBRARY) DATABASE, INCLUDING MEDLINE (MEDICAL LITERATURE ANALYSIS AND RETRIEVAL SYSTEM ONLINE) DATABASES AND LILACS (LATIN AMERICAN LITERATURE AND OF THE CARIBBEAN IN HEALTH SCIENCES), AND FINALLY, SCIELO (SCIENTIFIC ELECTRONIC LIBRARY ONLINE) IN PERIODICALS, BETWEEN 2010 AND 2017, IN THE PORTUGUESE LANGUAGE, CONTAINING A SAMPLE OF 10 ARTICLES THAT WERE ANALYZED. TWO CATEGORIES WERE STUDIED: NURSING ACTIONS ON SCREENING AND NURSING CARE FOR BREAST AND CERVICAL CANCERS. DISCUSSION: FROM THE STUDIES OF THE ARTICLES, SEVERAL ASPECTS WERE DETECTED THAT REFLECT THE ROLE OF THE NURSE IN THE ACTIONS OF SCREENING AND EARLY DIAGNOSIS OF CERVICAL AND BREAST CANCERS. AS WELL AS DIFFICULTIES FOR THE DEVELOPMENT OF THEIR WORK. THE NURSE THROUGH THE NURSING CONSULTATION DEVELOPS ACTIONS AND PROVIDES CARE FOR GUIDELINES FOR PROMOTION, PREVENTION, CLINICAL BREAST EXAMINATION AND COLLECTION OF COLPOCITOLOGICAL, IMMUNIZATION AGAINST HPV, EARLY DETECTION OF ADVERSE EFFECTS OF TREATMENT, FAMILY ORIENTATION, REFERRALS OF REFERENCE AND AGAINST REFERENCE TO THE MULTIDISCIPLINARY TEAM AND THE ACTIVE SEARCH FOR PATIENTS WHO DO NOT ADHERE TO THE TREATMENT. CONCLUSION: WE BELIEVE THAT THE NURSE AS A MEMBER OF THE MULTIDISCIPLINARY TEAM DEVELOP ACTIONS OF PROMOTION, PREVENTION, EARLY DETECTION IN BREAST AND CERVICAL CANCER, AND THEIR ATTRIBUTIONS AND ACTIONS ARE SUPPORTED BY INSTITUTIONAL AND MS PROTOCOLS THAT SUPPORT THEIR WORK. THE WOMAN AND HER FAMILY ARE UNIQUE IN FACE OF THE TREATMENT AND THAT THE QUALIFIED AND HUMANIZED CARE IS INDISPENSABLE IN EVERY PHASE OF THEIR TREATMENT. IN THE LIGHT OF THE ANALYZED PAPERS, WE ARE APPREHENSIVE ABOUT THE REPORTS OF DIFFICULTIES FACED BY NURSING PROFESSIONALS IN THE NURSING CONSULTATION, SINCE THE AUTHORS REPEATEDLY PORTRAY THE LACK OF KNOWLEDGE AND / OR CAPACITY FOR CONDUCTING PREVENTIVE EXAMS AND SCREENING FOR CANCERS, AS WELL AS THE LACK OF RECEPTION, HUMANIZATION, ETHICS, RESOURCES, PRIVACY, AMONG OTHER ASPECTS THAT HINDER THE IMPLEMENTATION OF PUBLIC POLICIES.
Keywords: Early Detection. Nursing care. Role of the nurse